Sex differences in child and adolescent physical morbidity: cohort study. Issue 1 (29th December 2017) - Sweeting, Helen; Whitley, Elise; Teyhan, Alison; Hunt, Kate
Abstract : Background: Evidence on sex differences in physical morbidity in childhood and adolescence is based largely on studies employing single/few physical morbidity measures and different informants. We describe sex differences in a wide range of parent/carer-reported physical morbidity measures between ages 4 and 13 years to determine evidence for a generalised pattern of an emerging/increasing female 'excess'. Methods: Parents/carers (approximately 90% mothers) of the population-based UK ALSPAC cohort provided data on general health, physical conditions/symptoms and infections in their child approximately annually between ages 4 and 13. Logistic regression analyses determined the odds of each morbidity measure being reported in respect of females (vs males) at each age and the sex-by-age interaction, to investigate any changing sex difference with age. Results: Six measures (general health past year/month, high temperature, rash, eye and ear infections) demonstrated an emerging female 'excess', and six (earache, stomach-ache, headache, lice/scabies, cold sores, urinary infections) an increasing female 'excess' ; one (breathlessness) showed a disappearing male 'excess' . Just two showed either an emerging or increasing male 'excess'. Most changes were evident during childhood (prepuberty). Six measures showed consistent female 'excesses' and four consistent male ' excesses' . Few measures showed no sex differences throughout this period of childhood/early adolescence. Conclusion: Sex differences are evident for a wide range of parent-reported physical morbidity measures in childhood and early adolescence. Far more measures showed an emerging/increasing female 'excess' than an emerging/increasing male 'excess'. Further studies are required to examine whether patterns differ across sociodemographic/cultural groups, and to explain this generalised pattern.